ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA BERBASIS LITERASI SAINS DI SEKOLAH DASAR KOTA BULA SERAM BAGIAN TIMUR, MALUKU - Nanda, Dea Ariska; Ibrahim, Nurlaiha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Scientific literacy is an essential competency for elementary school students; however, many students still experience difficulties in solving PISA-oriented scientific literacy word problems. This study aimed to analyze the difficulties encountered by sixth-grade elementary school students in solving scientific literacy- based word problems on ecosystem balance and environmental conservation. A descriptive qualitative approach was employed involving 50 sixth-grade students from two public elementary schools. Data were collected through scientific literacy tests, interviews, and documentation, and analyzed using content analysis. The findings revealed that students experienced difficulties across three scientific literacy competencies: explaining phenomena scientifically, evaluating scientific inquiry and interpreting data and evidence, and using scientific information to make decisions. High-achieving students generally understood the problem context but were not yet consistent in using scientific evidence to support their answers. Moderate-achieving students had difficulties relating scientific concepts to evidence, while low-achieving students struggled to understand problem contexts, interpret data, and provide scientific reasoning. These findings indicate that students’ difficulties are associated not only with conceptual understanding but also with their ability to comprehend contextual information, interpret evidence, and apply scientific reasoning. The study suggests that science instruction should emphasize contextual and evidence-based learning activities to strengthen students’ scientific literacy and improve their ability to solve scientific literacy-based word problems